Inequities in Children’s Food Environment: A Comparison between Slum and Non-slum Settings in Urban Bangladesh - Tania Ahmed Chowdhury; Nasrin Akhter; Kaniz Fatima Emy; Akhi Akter; Ishrat Hossain; Rezwana Jahan; Mohammad Jahangir Alam; Pepijn Schreinemachers; Ee Von Goh (Journal of Urban Health, 2026)
Abstract Children living in urban slums face persistent nutritional and health inequities, many of which are rooted in the food environment. This study examined the drivers of children’s food behaviors in Dhaka, Bangladesh, comparing slum and non-slum settings through a cross-sectional survey of 300 mothers of school-aged children (8–12 years) and focus group discussions. Quantitative analysis revealed disparities in diet quality: children in non-slum areas had a 13% higher dietary quality score ( p < 0.001) and consumed 57% more servings of fruit and vegetables ( p < 0.001) than their peers in slum areas. Household income, maternal education, and monthly spending on fruits and vegetables were significant predictors of fruit and vegetable intake and dietary quality scores. Qualitative insights further showed that mothers in slum areas prioritized giving their children energy-dense, animal-source foods. In contrast, mothers in non-slum areas emphasized dietary diversity, including both animal- and plant-based foods, and tried to limit their children’s unhealthy food choices. Differences in food marketing exposure and inadequate school food environments further reinforced the observed differences in dietary behavior. Addressing these food inequities requires integrated urban nutrition strategies, including affordable access to fresh produce, regulation of food marketing to children, and strengthened school nutrition programs.